2014
DOI: 10.1016/j.ijhydene.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Expression of different types of [FeFe]-hydrogenase genes in bacteria isolated from a population of a bio-hydrogen pilot-scale plant

Abstract: production.An extensive analysis of the expression of [FeFe]-hydrogenases in the three best producer strains was achieved by RT-PCR, covering the complete set of known genes for each species.This revealed that during H2 production there are several different [FeFe]-hydrogenases simultaneously expressed, with genes belonging to the same phylogenetic and structural classification sharing similar transcriptional profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 70 publications
2
45
0
Order By: Relevance
“…the exploitation of a novel hydrogenase recently isolated from a highly productive hydrogen pilot-plant fed with waste material [22,23], is strengthening the efforts towards a systematic identification of ideal biocatalysts to grant sustainable energy production. 35 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the exploitation of a novel hydrogenase recently isolated from a highly productive hydrogen pilot-plant fed with waste material [22,23], is strengthening the efforts towards a systematic identification of ideal biocatalysts to grant sustainable energy production. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Recombinant expression of the hydrogenase CpHydA from Clostridium perfringens SM09 [22] was performed in E. coli 30 Rosetta2(DE3) as previously described [31] upon transformation of the competent cells with plasmid pECPF2655, obtained by ligating the entire coding sequence of CPF_2655 into the empty expression vector pECr1 [23,24] between NdeI and XhoI sites. After the induction, cells were incubated over night under pure argon flow to maintain anaerobic conditions in a water bath at 30°C.…”
Section: Recombinant Expression and Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In bioprocess, quantitative monitoring of hydrogenase enzymes is important and can provide more in-sight on the process performance. Several groups have described tools for hydrogenase monitoring at DNA and RNA levels and reported how quantitative analyses of hydrogenases can reveal important clues about the bioprocess performance8910. Previously our group reported the means to quantify Clostridium butyricum [Fe-Fe] hydrogenase at gene and transcript levels in an open bioprocess system10.…”
mentioning
confidence: 99%
“…The relationship between H 2 production kinetics and gene transcript levels of several Clostridium spp. isolated from continuous stirred tank reactor was investigated by Morra et al 9. The authors reported similar transcriptional profiles, but different H 2 evolution kinetics among the isolates indicating a post-transcriptional down regulation of clostridial hydrogenases9.…”
mentioning
confidence: 99%